PODCASTS IN THE SYSTEM OF TEACHING RUSSIAN TO STUDENTS OF UZBEKISTAN - Ibragimova Nilufar Tuychievna (International Scientific and Current Research Conferences, 2026)
This thesis examines the pedagogical value of podcasts in teaching Russian to university students in Uzbekistan. It argues that podcast-based instruction enriches listening practice, pronunciation, vocabulary growth, and communicative confidence through authentic speech and flexible repetition. The paper outlines classroom applications, criteria for selecting podcast materials, and typical learning tasks. It also discusses methodological limitations and concludes that podcasts are most effective when integrated with speaking, reading, and writing activities.